(untitled) (Ustozlar uchun, 2025)
This thesis explores the critical role of media literacy in the contemporary digital era. It emphasizes the importance of critical thinking, accurate information evaluation, responsible media consumption, and the ability to discern reliable from unreliable sources. By examining theoretical frameworks and empirical studies, the work highlights how media literacy empowers individuals, promotes informed citizenship, and mitigates the risks of misinformation and manipulation. Educational interventions and digital literacy programs are evaluated for their effectiveness in enhancing media competencies across diverse populations.